Association of Amniotic Fluid Index with Fetomaternal Outcomes - Nawaz, Afshan; Anbreen, Fauzia; Javed, Kiran; Ajaz, Maryam (Indus Journal of Bioscience Research, 2025)
Background: Amniotic fluid index is an established marker of fetal renal function, placental activity, and overall intrauterine well-being. Abnormal levels, particularly oligohydramnios, are associated with adverse pregnancy outcomes, including cesarean delivery and increased neonatal morbidity. Objective: To determine the association of low amniotic fluid index with adverse fetomaternal outcomes. Study Design: Cohort study. Duration and Place of Study: This study was conducted over six months, from December 2024 to May 2025, in the Department of Obstetrics and Gynecology, District Headquarters Teaching Hospital, Dera Ismail Khan. Methodology: A total of 228 women aged 18–40 years, carrying singleton pregnancies beyond 20 weeks, were included. Participants were categorized into two groups: exposed (AFI ≤5.0 cm) and unexposed (AFI 5.1–25 cm). Pregnancies with comorbidities or high-risk factors were excluded. Maternal outcome was assessed in terms of cesarean delivery, while neonatal outcome was evaluated by the requirement of NICU admission. Results: Cesarean delivery occurred in 46.5% of the exposed group compared to 6.1% of the unexposed group (p